Comparative Evaluation of Articaine and Lignocaine for Palatal Anaesthesia Following Buccal Infiltration in Maxillary Extractions. - Karunakaran, Sadhana; George.A, Melvin (Journal of Neonatal Surgery, 2025)
Background : Palatal injections administered during maxillary tooth extraction are often associated with significant discomfort and pain. Articaine, owing to its superior tissue diffusibility, may provide effective palatal anaesthesia following buccal infiltration alone and thereby reduce the need for painful palatal injections. This study compared the efficacy of Articaine and Lignocaine for palatal anaesthesia following buccal infiltration during maxillary tooth extraction. Materials and Methods : A prospective randomized comparative clinical study was conducted among 40 patients requiring maxillary tooth extraction. Participants were randomly divided into two groups of 20 each. One group received 4% Articaine with 1:100,000 epinephrine, while another Group received 2% Lignocaine with 1:100,000 epinephrine through buccal infiltration. Parameters evaluated included onset of anaesthesia, duration of anaesthesia, pain during administration of anaesthesia, pain during extraction, postoperative pain, and need for re-anaesthesia. Pain was assessed using the Visual Analog Scale (VAS). Statistical analysis was performed using SPSS software, and p < 0.05 was considered statistically significant. Results: The Articaine group demonstrated a significantly faster onset of anaesthesia (49.044 ± 7.098 seconds) compared to the Lignocaine group (93.150 ± 5.857 seconds) (p = 0.001). The duration of anaesthesia was significantly longer with Articaine (124.995 ± 6.972 minutes) than with Lignocaine (79.495 ± 12.102 minutes) (p = 0.001). Pain scores during administration, during the procedure, and after the procedure were consistently lower in the Articaine group. Re-anaesthesia was required in only 15% of patients receiving Articaine compared to 50% in the Lignocaine group (p = 0.020). Conclusion: Articaine demonstrated superior anaesthetic efficacy compared to Lignocaine by providing faster onset, prolonged duration of anaesthesia, improved pain control, and reduced need for supplemental palatal injections during maxillary tooth extraction. Articaine may therefore be considered an effective alternative to Lignocaine for maxillary dental extractions.